(untitled) (Research, Society and Development, 2023)
This narrative review aims to update the ethnopharmacology, phytochemistry and biological activities of Geissospermum species described in the literature, in order to contribute to the knowledge of bioactive compounds of therapeutic interest and establish directions for future research with this genus. The term “Geissospermum” was used to perform searches in different databases such as NDLTD (Digital Library Network of Theses and Dissertations), Google Scholar, PubChem, Scifinder, Web of Science, SciELO, PubMed and Science Direct. Google’s National Institute of Industrial Property and Patents (INPI) was also consulted. The keywords indole alkaloids, quina-quina, Geissospermum, Geissospermum reticulatum and malaria were used in the search. Publications in Portuguese, French, Spanish and English published between 1950 and 2022 were included. Indole alkaloids are the main secondary metabolites found in this genus, and several molecules have already been isolated, which may be related to the described pharmacological activities. Extracts and isolated compounds showed antitumor, antimalarial, antinociceptive, anti-inflammatory, anticholinesterase, anti-HIV, antimicrobial and antioxidant activity. Plants of the genus Geissospermum are used in Brazil mainly by the Amazonian peoples to treat various pathologies. Biological activities reported for extracts and isolated compounds are consistent with etonopharmacological use against malaria, cancer and other diseases. Future work with Geissospermum species is needed to elucidate the mechanism of action of the isolated alkaloids, as well as their toxicological profile.